Effect of Chitosan and Rice Starch Coating on the Kraft Paper - Roslizan, Nur Wahidatul; Hussin, Rosniza; Mohamad, Hasmaliza; Main, Nor Mazlana; Ibrahim, Siti Aida; Harun, Zawati (Emerging Advances in Integrated Technology, 2022)
The use of chitosan and rice starch as the bio-based coated paper has resulted in a positive effect on physical, mechanical, and optical properties. The research was to show the influence of ultrasonic treatment on the properties of bio-based coated paper. The influence of ultrasonic treatment on the kraft paper with coating solution was determined for the thickness, the tensile strength, and surface morphology analysis. The sample prepared has two types which are uncoated paper coated paper and coated with ultrasonic treatment paper. The coated paper with bio-based coatings has been applied by spray technique. One from both coated samples has been coated with a solution that has been treated. The result shows that the thickness and grammage for both coated papers increased between 0.01 mm to 0.03 mm. Tensile strength has been improved on both coated papers. The higher tensile strength obtained was from the sample in the machine direction, which is 8083.2 N/m. Furthermore, the ultrasonic treatment also gives an improvement in morphology. As expected, the coating gives a surface with fewer and smaller pores. From morphology analysis, the coated paper in which the solution has been treated was smoother, and few pores were detected. From the result, ultrasonic treatment is an environmentally inexpensive process and effective in preparing solutions for bio-based coating. The coatings give better mechanical and morphology properties. Therefore, preparation solution using ultrasonic treatment as pretreatment is an improvement to enhance many properties of bio-based coatings.